El turismo desde la perspectiva de la ciencia de redes: una aproximación desde la investigación a través del tiempo - Duarte Patiño, William Stevens (Universidad Antonio Nariño, 2021)
With the growing interest on the investigation of the tourism as a complex system, given the great relevance that this has become for the economic growth of countries, a new methodology has begun to be used to study this type of system, called as Network Science, this methodology allows us to understand these systems that involve different types of actors, to establish the nature under those specifics systems, while assessing the nature of the complex network structure of those systems in general. Taking into account this growing type of studies, it has been proposed in the present work the elaboration of a state of the art, which based on a collection of investigations under this type of approach, allows determining the tendencies and characteristics of this type of research. Thus determining possible future changes in the growth and development of these works through the meticulous analysis of various properties in the area of metadata and methodological approaches of the collected documents. Among the most notorious results, the versatility of tourism to function with different areas of knowledge is evident, the quality of these studies despite their recent appearance its commonly high, the great diversity of perspectives that can be addressed from this work methodology despite the restrictions in the scope and design of the works, together with other characteristics that allow a more detailed understanding of this type of research from a rigorous and detailed approach.